Monitoramento da carga interna de atletas de voleibol de praia antes, durante e após uma etapa do circuito nacional - Silva , Kalinne Fernandes (2021)
The monitoring of the internal load of training has been widely used in sports, in order to accurately quantify the application of training loads imposed by the coaching staff. However, few studies have investigated the monitoring of the internal load before competition (AC), during competition (CE) and after competition (PC) in beach volleyball. Therefore, the objective of this study was to monitor the internal load before competition, in competition, and post competition of beach volleyball athletes considering the player's position. Eight high performance beach volleyball athletes competing in national and world championships (23.1 ± 4.0 years old; 85.4 ± 11.1 kg; 190.3 ± 9.3 cm; 69.3 ± 9.5 kg of lean body mass; 11.8 ± 2.8 kg of fat mass; and 13.8 ± 3.0 %G), voluntarily participated in the study. During the four weeks of this study the monitoring of heart rate variability (HRV), vertical jump, training momentum (TRIMP) and subjective perception of effort (PSE) was performed. It was verified in the HRV that there was significant interaction in group x time (p<0.05) and in time (p< 0.05). However, in the comparative analysis of TRIMP, total accumulated load, weekly daily average and Strain there was no significant interaction in group x time (p> 0.05), however there was significant interaction in time (p< 0.05). Furthermore, it was observed that in the comparative analysis of monotony and vertical jump, there was no significant interaction in group x time (p> 0.05) and time (p> 0.05).